Incidence and risk factors for mechanical injuries caused by the transesophageal ultrasound probe manipulation in the setting of transfemoral transcatheter tricuspid repair. (4th February 2022) - Kuecken, T; Bannehr, M; Lalou, E; Haase-Fielitz, A; Butter, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Leading right heart failure due to tricuspid regurgitation results in retrograde hepatic venous congestion with subsequent gastropathy and hyperemia of the gastric mucosa. Due to increased portal pressure as well as possible cirrhosis cardiaque, the risk for esophageal varices is greatly increased. In addition, associated with atrial dilatation, these patients usually suffer from atrial fibrillation and receive an oral anticoagulation/ direct anticoagulation (OAC/DOAC) as insult prophylaxis. Heparinization with a target ACT > 250 seconds is necessary during transfemoral transcatheter tricuspid repair (TTTR). Alternation between transgastric and midesophageal view with the transesophageal ultrasound probe is usually performed to better guide TTTR. Sufficient wall contact is crucial for good imaging. All of these conditions increase the risk for periprocedural gastric and/or esophageal injury. Purpose: The aim of this study was to assess the incidence and risk factors for mechanical irritation and bleeding caused by the TEE probe manipulation in the setting of TTTR. Methods: In this prospective cohort study patients received gastroscopy preinterventional and on the first day after TTTR. Statistical analysis was performed with IBM SPSS.28, t-Test was used to compare patients with and without postinterventional lesions. Results: From December 2020 to July 2021, 18 patients with indication for TTTR were included in this study. The mean age of the patients was 77.8 (± 7.5) years. Thirteen patients (72.2%) had antral gastritis and 4 patients (22.2%) had corpus gastritis preinterventionally. Esophageal varices were not detectable in any patient. Postinterventionally, 10 patients (55.6%) showed lesions (hematoma or coagulated pressure points) (Fig. 1), and 2 patients (11%) required interventional treatment with hemoclips. The main lesion sites were midesophageal at 20-25 cm, 1 lesion at the Z-line. A mean of 5.7 (± 2.5) position changes took place; the mean procedural duration was 88 (± 27.8) min. The number of clips placed (p = 0.64), the procedural duration (p = 0.99) and the number of position changes (p = 0.48) did not differ between the group of patients with and without injuries after TTTR (Tab 1). Conclusion: More than 50% of patients with TTTR showed postprocedural injuries (lesions) of the esophagus. Contrary to our assumption, mainly lesions midesophageal could be detected. Due to the procedure as well as the severe underlying disease, gastrointestinal bleeding is a potential complication in the context of a TTTR. Consideration should be given to implementing regular control gastroscopy after TTTR to reduce the procedure-related complication rate. Due to the high incidence of procedure-related lesions, further research in larger patient collectives is necessary.